Measuring Learning : How Effective Student Assessment Systems Can Help Achieve Learning for All - Clarke, Marguerite (World Bank, Washington, DC, 2012)
The importance of learning assessment is linked to growing evidence that learning drives prosperity. Research finds a one standard deviation increase in scores on international assessments of reading and mathematics is associated with a 2 percent point increase in annual growth rates of Gross Domestic Product (GDP) per capita (Hanushek and Woessmann, 2007). This brief includes the following headings: challenges to assessing student learning; what do assessment systems look like?; Effective assessment systems; and reference.